2020
DOI: 10.1038/s41467-020-17952-5
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR GUARD protects off-target sites from Cas9 nuclease activity using short guide RNAs

Abstract: Precise genome editing using CRISPR-Cas9 is a promising therapeutic avenue for genetic diseases, although off-target editing remains a significant safety concern. Guide RNAs shorter than 16 nucleotides in length effectively recruit Cas9 to complementary sites in the genome but do not permit Cas9 nuclease activity. Here we describe CRISPR Gu ide RNA A ssisted R eduction of D amage (CRISPR GUARD) as a method for protectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Efforts were made to develop more specific Cas9•sgRNA systems and systems that activate homology-directed repair instead of non-homologous end joining [93,[98][99][100]. Recent approaches reduce off-target effects by co-delivery of short sgRNAs directed against off-target loci [101]. Other strategies involve using Cas9 orthologues from other organisms, using directed evolution and protein engineering to develop improved Cas9 variants or applying different CRISPR/Cas types [60,[102][103][104][105].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts were made to develop more specific Cas9•sgRNA systems and systems that activate homology-directed repair instead of non-homologous end joining [93,[98][99][100]. Recent approaches reduce off-target effects by co-delivery of short sgRNAs directed against off-target loci [101]. Other strategies involve using Cas9 orthologues from other organisms, using directed evolution and protein engineering to develop improved Cas9 variants or applying different CRISPR/Cas types [60,[102][103][104][105].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the use of CRISPR/Cas9 RNP instead of a plasmid vector, reduced the risk of off-target mutations as RNP is cleared from the cells within 24 hours after transfection ( DeWitt et al, 2017 ). Furthermore, other methods are in development to minimize the off-target effects such as CRISPR Guide RNA Assisted Reduction of Damage (GUARD) that protects off-target sites by co-delivering short gRNAs directed against off-target loci by competition with the on-target gRNA without affecting on-target editing efficiency ( Coelho et al, 2020 ). Nonetheless, it would be appropriate to investigate off-target mutations in animals, embryos or somatic cells as deeply as possible using methods for identification of off-target sites, such as whole genome sequencing (WGS) and whole-exome sequencing (WXS) ( Ishii, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Coelho and colleagues have developed CRISPR GUARD strategy to reduce Cas9 off-target effects without decreasing on-target editing efficiency. The results from BLI demonstrated that the majority of off-targets were protected by CRISPR GUARD molecule [ 32 ]. In our study, the off-target effect of 2LTRZFP-GFP was determined to observe whether 2LTRZFP-GFP can exhibit non-specific binding towards human Chromosome using BLI system.…”
Section: Discussionmentioning
confidence: 99%